Simultaneous Bilateral Carotid Thrombectomies: A Technical Note. Issue 5 (23rd August 2019) - Larrew, Thomas; Hubbard, Zachary; Almallouhi, Eyad; Banerjee, Chirantan; Moss, Mark; Spiotta, Alejandro M
Abstract: BACKGROUND: Although extremely rare, acute bilateral large vessel occlusion (LVO) is a morbid condition that requires prompt intervention. OBJECTIVE: To report the technique used to achieve recanalization of bilateral internal carotid artery (ICA) terminus occlusions. METHODS: This is a case of bilateral ICA terminus occlusions managed with simultaneous bilateral thrombectomies with poor collateral circulation. RESULTS: Recanalization of bilateral ICA with thrombolysis in cerebral infarction (TICI) grade 0 to left TICI 2b flow with distal left A1 occlusion and right TICI 3 flow was achieved in 32 min with the use of simultaneous catheterization and aspiration thrombectomies. CONCLUSION: The described technique offers an efficient and feasible means to reduce time to recanalization and radiation in cases of bilateral LVO.